Implementation of the Al-Bayan Learning Method to Improve Children's Quran Reading Skills - Aina Salsa Bela; Nita Yuli Astuti; Fihris (South Sulawesi Education Development (SSED), 2024)
Mastery of Tajweed is the key to reading the Qur'an correctly and deeply. This study focuses on the use of the Al-Bayan method in improving the ability to read the Qur'an in children at TPQ Bani Mukmin, Kedungtulup, Central Java. The Al-Bayan method is a learning approach designed to help students understand Tajweed and read the Qur'an correctly and quickly. This study aims to evaluate the effectiveness of the method in improving students' ability to read the Qur'an. This study uses a qualitative approach with observation, interview, and documentation techniques as data collection methods. The subjects of the study were students and teachers at TPQ Bani Mukmin. The analysis was conducted to measure the impact of the Al-Bayan method on the development of students' reading skills, especially in the application of Tajweed. The results of the study showed that the Al-Bayan method was effective in significantly improving the ability to read the Qur'an. Students were able to understand and apply Tajweed better in a relatively short time. The interpretation of these results indicates that the Al-Bayan method can be widely used as an efficient Qur'an learning solution in elementary education environments.